1991
DOI: 10.1002/eji.1830210938
|View full text |Cite
|
Sign up to set email alerts
|

Late treatment with anti‐LFA‐1 (CD11a) antibody prevents cerebral malaria in a mouse model

Abstract: CBA/Ca mice injected with Plasmodium berghei develop cerebral malaria (CM) characterized by ataxia and progressive paralysis leading to death 7-9 days after experimental infection. The development of cerebral symptoms is a function of the immune response in susceptible strains, and depends on cell-cell interactions involving T helper cells and mononuclear phagocytes. Here we ask whether antibodies to cell adhesion receptors of the immune system can influence the development of CM in this mouse model. When admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
39
1

Year Published

1991
1991
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 32 publications
4
39
1
Order By: Relevance
“…Numerous studies have illustrated that activated T cells that are sequestered in the brain contribute to CM (8,27). Treatment of mice with anti-LFA-1 mAb inhibiting LFA-1/ICAM-1 interaction and thereby adhesion of T cells to the endothelium prevents mice from developing CM (28,29). Moreover, the development of CM in PbA-infected C57BL/6 mice is strongly dependent on the production of proinflammatory cytokines during the course of infection (11,30).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have illustrated that activated T cells that are sequestered in the brain contribute to CM (8,27). Treatment of mice with anti-LFA-1 mAb inhibiting LFA-1/ICAM-1 interaction and thereby adhesion of T cells to the endothelium prevents mice from developing CM (28,29). Moreover, the development of CM in PbA-infected C57BL/6 mice is strongly dependent on the production of proinflammatory cytokines during the course of infection (11,30).…”
Section: Discussionmentioning
confidence: 99%
“…This pathogenic hypothesis is supported by the increased expression of CD54 and CD106 in the brain microcirculation during SM and the delayed mortality seen in mice treated with anti-CD11a mAb (LFA-1, a ␤2 integrin determinant) 6,17 or in CD54-deficient mice. 18 CD40 is a cell receptor belonging to the TNF receptor superfamily that can modulate cell proliferation, differentiation, and death. 19 Studies based on mice genetically deficient in CD40 or its ligand CD40L (CD154) as well as the use of anti-CD40L mAb have demonstrated that this system plays an important role in both humoral and cellmediated immunity.…”
mentioning
confidence: 99%
“…Upregulation of ICAM-1 expression in the vascular endothelium is reported for human (24), simian (25), and murine (26,27) severe malaria. It has been demonstrated that ICAM-1 is coexpressed with CD36, thrombospondin, VCAM-1, and E-selectin on the brain microvasculature of postmortem samples of patients who had died of cerebral malaria.…”
Section: Discussionmentioning
confidence: 94%
“…It was found to bind IRBC in vitro (7). During acute-phase malaria, ICAM-1 is expressed by the vascular endothelium of the brain (24)(25)(26)(27). In the SCID mice used as Plasmodium hosts in these experi- ments, acute-phase ICAM-1 expression was induced by treatment with LPS.…”
Section: Resultsmentioning
confidence: 99%